Effects of Dyadic Quality and Duration on Performance Appraisal - Duarte, Neville T.; Goodson, Jane R.; Klich, Nancy R. (Academy of Management Journal, 1994)
This study examined the interactive influence of performance, the quality of a supervisor-subordinate relationship, and the duration of that relationship on performance ratings. The results suggest that, in both the short run and long run, the performance of employees in high- quality “leader-member exchange” relationships is rated high, regardless of their objectively measured performance. The ratings of employees in low-quality exchange relationships are consistent with their objective performance in the short run but high in the long run, regardless of objective performance.